Pengaruh Metode Tanya Jawab Terhadap Hasil Belajar Siswa - Yayan Abdika; Muhammad Amir Arham; Sudirman Sudirman (Jambura Economic Education Journal, 2019)
ABSTRACT Yayan Abdika,Student ID 911415115 “The Influence of the Question and Answer  Method on Students”  UnderGraduate Thesis. Department of Economic Education, Faculty of Economics Universitas Negeri Gorontalo., 2019. The Purpose of the Study is to find out “The Influence of the Question and Answer  Method on Students. The Method Used in this Study was a quantitative method with population of 103 students from a population of 30 students. Further, data collection techniques used primary and secondary data, primary data obtained directly in the field through questionnaires and observations and secondary data obtained were from data that has been processed or throught literature. This study employed simple regression with a series of statatical tests. The Results of the analysis showed that there is a positive and significant effect of the question and answer method on students learning outcomes, thus each change in the unit of question and aswer method would improve the learning outcomes. The regression results shows that 43.2% can be explained while the remaining 56.8% is explained by other variables Keyword : Question and Answer Method, Students, Learning Outcames